Multiple Criteria Decision-Making Methods : Applications for Managerial Discretion - Anand, Adarsh; Agarwal, Mohini; Aggrawal, Deepti (De Gruyter series on the applications of mathematics in engineering and information sciences, 2022)
This book provides application of multi criteria decision making techniques for managerial discretion. With this book, a concerted platform has been provided for several peers and other management organizations to understand and implement these tools and deal with the practical problems in a better way so as to provide more robust managerial decision making.